EFFECTIVE METHODS OF SYNCHRONOUS AND ASYNCHRONOUS COMPUTER SCIENCE TRAINING - Madyarova Г.А.; Adamova Қ.А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
Currently, large-scale changes are taking place in the education system, associated with the parallel conduct of online and distance, traditional education. These changes will allow students to widely use platforms, resources, educational materials for online and distance learning at many global and domestic levels. Nevertheless, the tools and techniques developed in the native language, their optimal use, independent performance of tasks and ensuring consistency in order to improve the quality of knowledge are not enough. In this regard, along with the choice of a systematic and effective, necessary, suitable platform, we consider one of the most pressing issues to create a complex in accordance with the content of training. The place of electronic educational resources in the scientific work of scientists has been studied. The possibilities of synchronous and asynchronous learning in improving the quality of learning are analyzed, their advantages and disadvantages are revealed. The article examines the main problems of the organization of synchronous and asynchronous education. Based on this, a model of the technological structure of asynchronous computer science training was developed. The I-Learning application has developed and tested a comprehensive course of synchronous and asynchronous computer science training for Grade 9. This article also demonstrates the positive results of the experiment.